Making of the Multimedia Document “Around the World in 80 Days“ - Perić, Katarina; Nikolić, Ana; Gogić, Kristina (Infotheca - Journal for Digital Humanities; Vol 15 No 2 (2014): Infotheca - Journal for Digital Humanities, 2024)
This text will present the process of the making of the class of 2014/2015’s multimedia document within the subject of the same name at the final year of the undergraduate studies at the Library Science and Information Technology Department within the Faculty of Philology of the Belgrade University. The document is divided into three parts: first part includes the author’s biography, second part includes the summary of the book and third part describes the technical realisation of the project and includes information on the project itself. Third part, being the most important one, will most fully explain the students’ research process; informational procedures such as planning, processing, designing and creating the multimedia document itself.